2023
DOI: 10.1186/s12880-023-01026-1
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and peritumoral MRI radiomics assisted in predicting radiochemotherapy response in metastatic cervical lymph nodes of nasopharyngeal cancer

Abstract: Background To establish and validate radiomic models combining intratumoral (Intra) and peritumoral (Peri) features obtained from pretreatment MRI for the prediction of treatment response of lymph node metastasis from nasopharyngeal cancer (NPC). Methods One hundred forty-five NPC patients (102 in the training and 43 in the validation set) were retrospectively enrolled. Radiomic features were extracted from Intra and Peri regions on the metastatic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Recently, a study revealed the heterogeneity of tumor microenvironment (TME) via virtual microdissection of gene expression profiles, which classified patients into 3 subgroups(Chen et al 2021 ), though it did not utilize the medical imaging generated from each patient. Another study demonstrated the potential significance of peritumoral regions of MRI in the treatment response of lymphatic node metastasis(Xu et al 2023 ). Despite encouraging results, the study cohort only recruited 145 patients and only explored 2 mm dilation, reaching an AUC of 0.78 in the clinic combined with radiomics model in the testing set.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study revealed the heterogeneity of tumor microenvironment (TME) via virtual microdissection of gene expression profiles, which classified patients into 3 subgroups(Chen et al 2021 ), though it did not utilize the medical imaging generated from each patient. Another study demonstrated the potential significance of peritumoral regions of MRI in the treatment response of lymphatic node metastasis(Xu et al 2023 ). Despite encouraging results, the study cohort only recruited 145 patients and only explored 2 mm dilation, reaching an AUC of 0.78 in the clinic combined with radiomics model in the testing set.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported on models constructed using radiomics features from the lymph nodes and briefly introduced the method for lymph node delineation in patients with NPC [ [21] , [22] , [23] , [24] , [27] , [28] , [29] , [30] , [31] , [32] ]. Xu et al [ 27 ] employed intra- and peritumoral MRI radiomics directly extracted from the largest metastatic lymph node to predict treatment response in patients with NPC. Lam et al [ 28 ] revealed that CT-based radiomics based on all metastatic lymph nodes was capable of predicting radiotherapy-related events in patients with NPC.…”
Section: Discussionmentioning
confidence: 99%